Design of hydraulic structures in supercritical regime with sediments: A mathematical criterion to calculate bottom roughness - Gracia-Sánchez, Jesús; Fuentes-Mariles, Oscar Arturo; Ramos, Judith (Tecnología y ciencias del agua, 2025)
In some channels with high gradients, heavy scouring and erosion, as well as overflow, is highly common to occur, thus it is required a water flow velocities regulation. An option for achieving this, is to significantly increase the channel’s bottom roughness through the installation of rapid hydraulic structures. However, in sedimentary density fluids, the change in velocity generates the deposition of solids which could be consolidated by changing the geometric design of these structures. This study aims to estimate the degree of confidence expected when modifications are made to the artificial roughness geometries at the bottom of the channel with turbulent and sediment flows. This modification requires to transverse the ribs into ramps by using experimental mathematical analysis. The study enables us to conclude that the new generated bottom roughness produces more stable water flows, and t is also a way to reduce flow velocities.